Benefits of the Tracers Test Technique in Improving the Performance of Group Wells - Putra, Dike Fitriansyah; Umar, Mursyidah; Futur, Lazuardhy Vozika; Rahman, Aznil Arif (Journal of Earth Energy Engineering, 2021)
This study aims to determine the benefits of the interwell tracer test technique in improving the streamline simulation on the existing array's re-look. It also analyses the best scheme for the injection spot to enhance oil recovery. This study's subject parameters are limited to the tracer's breakthrough time, produced concentration, cumulative production, and pathline movement. The results showed that previous studies distinguished the correlation between injectors and producers with the development of a new pathline that conveys a scheme of water-flood for the application. Furthermore, several developments of water-flood schemes have been executed for better oil recovery in the mature fields worldwide. The vigorous simulation model is an effort to imitate the actual field capable of enhancing the character's understanding and helping the waterflood to rinse the oil trap or the unswept pocket. Unlike a Cartesian model, the streamline conveys an enhanced portrait of the transmissibility reservoir in terms of pressure-driven. The streamline model suggests the injector's preferred position to unlock any unswept oil in the formation and minimize the water path conflict, which leads to over injection in some regions. The expected outcome is the ultimate oil increment with the original technique associated with re-patterning the wells appropriately to gain residual oil saturation in the virgin alleyway.